Quality Rated Childcare Programs and Social Determinants of Health in Rural and Non-Rural Georgia - Nancy Webb; Madison Gates (Georgia Southern University, 2016)
Background: Early childhood is linked to school readiness and early school achievement. Through its Quality Rated (QR) program, which was designed to improve the quality of care in early childhood programs, the state of Georgia has been a trailblazer in funding universal preschool and in improving the quality of childcare programs. We have assessed differences in the availability of QR childcare programs in Georgia to learn if, in rural versus non-rural counties, there is a relationship between QR childcare programs and health-related outcomes. Methods: This cross-sectional study evaluated county-level data to evaluate the relationship between QR childcare programs and social determinants of health. County-level data for Georgia were extracted from the Georgia Department of Early Care and Learning, County Health Rankings and Roadmaps, and the Georgia Juvenile Justice Data Clearinghouse. Results: Counties without QR childcare programs had child mortality rates 3.5 times higher than those for the state overall. Other differences in health-related outcomes included, but were not limited to, teen birth rates, low birth-weight babies, children in poverty, housing problems, and food insecurity. Conclusions: It is now appropriate to address the prevalence of health disparities in rural areas of Georgia and focus on some of the disparities through the QR early childhood programs and other state agencies. Empowering rural communities to address health disparities may be the most favorable path toward diminishing these inequalities.